"La parola di Dio è il fondamento di tutto". Esegesi storico-critica ed ermeneutica teologica secondo Joseph Ratzinger – Benedetto XVI - Prato, Ezio (Verbum Vitae, 2024)
Ratzinger’s reflections on biblical hermeneutics can be studied using different approaches. Three are the main ones: the ironical approach, a biographical one and, finally, a content-based one. Here, we will focus on the third approach, examining Ratzinger’s frequent comparison of the historical-critical method with the need to integrate it with a more specifically theological dimension of exegesis. Ratzinger has on several occasions traced a “history of the effects” of the historical method, also paying attention to its problematic aspects. In light of this history, the historical-critical method, while still indispensable, also proves to be insufficient. A careful consideration of its limits pushes towards a “self-critique of the method,” a “criticism of criticism ,” that highlights the faith-reason relationship implied and its philosophical presuppositions (the philosophical shift introduced by Kant). Rethinking biblical hermeneutics in the entirety of its dimensions (along the lines of what is proposed in Dei Verbum, no. 12) requires an adequate consideration of the properly theological depth of Scripture itself. This consideration involves, among other things, attention to the link between Scripture and Tradition and its relationship to the Church. In conclusion, three directions of research are indicated within Ratzinger’s theology and beyond its borders, in order to resume, extend and deepen some ideas that emerged from Ratzinger’s reflection on the problem in question.